Exercise and gastrointestinal symptoms: running-induced changes in intestinal permeability and markers of gastrointestinal function in asymptomatic and symptomatic runners - Karhu, E.; Forsgård, R. A.; Alanko, L.; Alfthan, H.; Pussinen, P.; Hämäläinen, E.; Korpela, R. (European Journal of Applied Physiology, 2017)
Purpose: Athletes frequently experience gastrointestinal (GI) symptoms during training and competition. Although the prevalence of exercise-induced GI symptoms is high, the mechanisms leading to GI distress during exercise are not fully understood. The aim of this study was to identify running-induced changes in intestinal permeability and markers of GI function and investigate their association with gastrointestinal symptoms. Methods: We recruited 17 active runners who we allocated as either asymptomatic or symptomatic based on their history of experiencing GI symptoms during running. The participants took part in a running test where they were asked to run for 90 min at 80% of their best 10 km race speed. Intestinal permeability was measured at baseline and after the running test. Levels of serum intestinal fatty acid-binding protein (I-FABP), zonulin, bacterial lipopolysaccharide (LPS), and fecal calprotectin were also measured at baseline and after the running test. Results: Running induced a significant increase in intestinal permeability and serum I-FABP concentration but there were no differences between asymptomatic and symptomatic runners. Serum LPS activity did not change from baseline following the running test but the symptomatic group exhibited higher LPS activity at baseline compared to the asymptomatic runners. Conclusions: Running for 90 min at a challenging pace causes small intestinal damage and increases intestinal permeability. However, these alterations in GI function do not appear to correlate with the development of GI symptoms during running.